Spatiotemporal analysis and interpretation of 1993–2013 ground deformation at Campi Flegrei, Italy, observed by advanced DInSAR. Issue 17 (2nd September 2014) - Samsonov, Sergey V.; Tiampo, Kristy F.; Camacho, Antonio G.; Fernández, José; González, Pablo J.
Abstract Campi Flegrei is one of the most hazardous volcanic areas in the world because of its close proximity to the city of Naples. Here we apply the multidimensional small baseline subset (MSBAS) differential interferometric synthetic aperture radar (DInSAR) technique to obtain vertical and horizontal components of ground deformation for Campi Flegrei at high spatial and temporal resolutions that span, for the first time, 20 years. The area underwent continuous subsidence from 1993 through 1999. Moderate uplift began in 2010 and substantially increased through 2012, reaching approximately 13 cm by 2013. We model the observed deformation to determine source parameters for subsidence and uplift epochs. Both the inflation and deflation mechanisms involve large, extended sources in a layered hydrothermal system whose location is controlled by the caldera structure and stratigraphy. The temporal resolution of MSBAS approaches that of GPS daily time series, with superior precision and spatial resolution, making it an excellent alternative for volcano monitoring.